INFLUENCE OF SEED QUALITY AND TYPE OS SUBSTRATE ON PLANT FORMATION OF ESPINHEIRA-SANTA - KOWALSKI, Ana Paula de Jesus; SIGNOR, Diana; MACHADO, Eliana Márcia; BIASI, Luiz Antonio; LIMA, Daniela Macedo de (Scientia Agraria, 2008)
Espinheira-Santa (Maytenus ilicifolia), a Brazilian native species, is largely used by the population as well as for the phytotherapeutic industry. The objectives of this work were to evaluate the influence of seed weight, different fruit stage to collected, and the use of different substrates on the Maytenus ilicifolia plantlets development. Seeds used for the experiments were obtained from 6-year-old plants of Estação Experimental do Canguiri, Federal University of Paraná (UFPR), Pinhais-PR, in January, 2006. In the first experiment, seeds were collected from fruits which were opened. Fresh matter of the seeds was individually determined and the seeds were sown in tubes containing Plantmax HT®. In the second experiment, organic compost mixtures were tested (0, 25, 50 e 75%), in mixture to the soil. In the third experiment, seeds were collected from opened fruits, which had their arils and seeds exposed, and from closed fruits presenting the typical orange to red color. The fresh matter of seeds did not influence plantlets development. Plantlets obtained in soil with organic compost mixtures produced larger numbers of leaves than soil alone in all mixture proportions tested, but offered no influence on plant survive. There was no difference in plant survive or initial plantlet development between the seeds obtained from opened or closed fruits. Average plant survive was 88,95%.